The Effects of Financial Ratio and Market Based Ratio toward the Stock Price of Manufacturing Industry Sector in Indonesia Stock Exchange - Mulyono Mulyono (Bina Nusantara University, 2015)
The research objectives to examine the magnitude of the significant influence between financial ratios and the market based ratio toward the stock price of manufacturing industry sector in Indonesia Stock Exchange (IDX). In accordance IDX data by December 2013, the number of companies, included in the stock of the manufacturing industry sector, is 139 companies. Based on the analysis, it is concluded that the variable return on assets (ROA) and price to book value (PBV) has positive influence on stock prices. It can be interpreted that the higher the return on assets ratio and price to book value, the more positive influence on the increase of the stock price. The variable debt to equity ratio (DER) and price earnings ratio (PER) has negatively influence the stock price on the stock of manufacturing industry sector. This can be interpreted the higher the value of the debt to equity ratio and price earnings ratio, the more negatively influence on the decrease stock price.